The Identification of Octocorals from the Northern Region of Straits of Malacca - Mahadi Mohammad,; Zaharatul Naa'imah Apandi,; Hana Abdul Wahab Marican,; Nadthikphorn Kamphol,; Nur Ain Amani Abdul Mubin,; Sazlina Salleh,; Md Nizam Ismail, (Tropical Life Sciences Research, 2016)
Coral reefs in the northern region of the Straits of Malacca have a diverse group of octocorals growing on its bed. The octocorals identified in this study are from islands along the Straits. In this study, 23 specimens were identified, belonging to 4 sub-orders, which have been subdivided into 8 families. From these 8 families, 15 different genera have been identified. The identification process for this research was conducted based on five important keys; the external form and colouration, polyps or colonial and fundamental structure of colonies, monomorphic or dimorphic, the arrangement of polyps, and the arrangement of sclerites.